The relationship between spiritual health and attitude towards death in family caregivers of COVID-19 patients discharged from the Intensive Care Unit of hospitals affiliated to Tehran University of Medical Sciences in 2021 - Zeinab Siami; Mostafa Taheri (Tehran University of Medical Sciences, 2024)
Background & Aim: Family caregivers of COVID-19 patients in the Intensive Care Units (ICUs) face numerous challenges that can affect their well-being. Spiritual health represents a crucial component for coping with such stressful conditions. Therefore, this study aims to determine the relationship between spiritual health and attitude towards death in family caregivers of COVID-19 patients post-discharge from the ICUs. Methods & Materials: This descriptive-correlational study conducted between April and November 2021, focused on family caregivers of COVID-19 patients discharged from the ICUs. The sample comprised 260 family caregivers selected through convenience and purposive sampling methods. Data collection tools included a demographic and clinical questionnaire, Polotzin and Ellison's Spiritual Health Questionnaire, and Wong's Death Attitude Questionnaire. Data were analyzed using SPSS version 24 encompassed chi-square tests, one-way analysis of variance and Spearman correlation coefficient. Results: The results showed a significant inverse relationship between total spiritual health score and the total score of attitude towards death (rs=-0.101, P<0.05). The attitude towards death findings revealed fear as the highest scoring dimension, with active acceptance scoring the lowest. Moreover, religious health exhibited a significant inverse relationship with avoidance of death (rs=-0.93) and fear of death (rs=-0.64, P<0.05). Conclusion: The study highlighted an inverse relationship between the level of religious health and negative dimensions of attitude towards death. Individuals with higher religious health scores exhibited lower average scores for negative attitudes towards death, including fear and avoidance of death. This underscores the importance of emphasizing the religious dimension within families, and among patients discharged from the ICU, showcasing the role of religion in mitigating negative attitudes towards death.